Intraocular inflammation and presumed retinal vasculitis following initial pegcetacoplan intravitreal injection - Seela, Josephine R.; Zubair, Talhah; Vagaggini, Tommaso; Williams, David F. (Digital Journal of Ophthalmology, 2026)
We report a case of presumed retinal vasculitis and precipitous complete vision loss following a single intravitreal injection of pegcetacoplan. A 76-year-old woman received intravitreal pegcetacoplan in the right eye for geographic atrophy. Visual acuity was 20/50 right eye. Ten days after the injection, she experienced initial signs of subjective vision loss. On day 11, she presented with elevated intraocular pressure and visual acuity of hand motions, worsening to no light perception (NLP) by day 12. Anterior chamber and vitreous fluid taps for Gram stain and culture were negative. On day 22, the patient had diffuse retinal hemorrhages along a retinal vascular distribution. At day 83, visual acuity remained NLP. This patient developed presumed occlusive retinal vasculitis, progressing from visual acuity of 20/50 to NLP within 2 days of initial subjective vision loss and 12 days of a single intravitreal pegcetacoplan injection.